Perlindungan HAM bagi masyarakat dalam menyuarakan keadilan melalui kebebasan berekspresi di Indonesia: indonesia - azizz, m alvin (Maliki Interdisciplinary Journal, 2026)
Protection of human rights (HAM) related to freedom of expression is one of the main foundations of a democratic system, including in Indonesia. This freedom provides an opportunity for the public to express their views, provide criticism, and express expectations regarding public policies without fear of repressive action. However, in reality, freedom of expression often faces various obstacles, such as criminalization, restrictions through regulations, and social and political pressure. This study aims to explore how human rights protection is provided to the public in expressing justice through freedom of expression in Indonesia. The methodology used is a qualitative approach with a literature review of various regulations, journals, and relevant cases. The research findings indicate that normatively, Indonesia already has a fairly solid legal basis to ensure freedom of expression, reflected in the 1945 Constitution and regulations related to human rights. However, empirically, its implementation is still far from optimal. Therefore, strengthening regulations, fair law enforcement, and increasing public awareness are needed to create space for healthy and responsible freedom of expression. In addition, it is also important to strengthen the role of state institutions and independent institutions in guaranteeing the protection of freedom of expression. Law enforcement officials are expected to act professionally, proportionally, and non-discriminatory in handling cases related to the expression of opinion.